2019
DOI: 10.1177/0003702819881762
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Raman Analysis in Biological Tissues Using Dual-Wavelength Excitation Raman Spectroscopy

Abstract: A dual-wavelength excitation Raman probe with laser inputs at 866 nm or 1064 nm is customized and integrated into a compact Raman spectrometer that is based on an InGaAs detector. Under 1064 nm illumination, the spectrometer detects fingerprint Raman signals below 2000 cm–1. While under 866 nm illumination, the spectral range is extended to cover high-frequency region (2400–4000 cm–1) that includes major C–H and O–H Raman vibrations. We demonstrate that the dual excitation InGaAs Raman is beneficial in detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Raman spectra were acquired with a customized dual-wavelength Raman spectrometer based on an InGaAs detector (Du490A, Andor) and a compact spectrograph (Wasatch Photonics) with a fixed range of 1,092-1,345 nm, the detail of this setup was described in a technique note published elsewhere. [24] Briefly, a tunable Ti:Sapphire laser (3900S, Spectra Physics) operated at 866 nm delivering~50-mW light on the sample surface and a diode-pumped laser (l0164mm0500MF, Innovative Photonics Solutions) operated at 1,064 nm delivering~80-mW light on sample were used as the excitation sources. A short pass filter (FESH900, Thorlabs) and a laser line filter (LL01-1064-12.5, Semrock) were used to clean the 866 nm and the 1,064-nm laser, respectively, and a dichroic beamsplitter (Di02-R1064-25x36, Semrock) is used to set up Raman system with back-scattering configuration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Raman spectra were acquired with a customized dual-wavelength Raman spectrometer based on an InGaAs detector (Du490A, Andor) and a compact spectrograph (Wasatch Photonics) with a fixed range of 1,092-1,345 nm, the detail of this setup was described in a technique note published elsewhere. [24] Briefly, a tunable Ti:Sapphire laser (3900S, Spectra Physics) operated at 866 nm delivering~50-mW light on the sample surface and a diode-pumped laser (l0164mm0500MF, Innovative Photonics Solutions) operated at 1,064 nm delivering~80-mW light on sample were used as the excitation sources. A short pass filter (FESH900, Thorlabs) and a laser line filter (LL01-1064-12.5, Semrock) were used to clean the 866 nm and the 1,064-nm laser, respectively, and a dichroic beamsplitter (Di02-R1064-25x36, Semrock) is used to set up Raman system with back-scattering configuration.…”
Section: Methodsmentioning
confidence: 99%
“…Raman spectra were acquired with a customized dual‐wavelength Raman spectrometer based on an InGaAs detector (Du490A, Andor) and a compact spectrograph (Wasatch Photonics) with a fixed range of 1,092–1,345 nm, the detail of this setup was described in a technique note published elsewhere . Briefly, a tunable Ti:Sapphire laser (3900S, Spectra Physics) operated at 866 nm delivering ~50‐mW light on the sample surface and a diode‐pumped laser (l0164mm0500MF, Innovative Photonics Solutions) operated at 1,064 nm delivering ~80‐mW light on sample were used as the excitation sources.…”
Section: Methodsmentioning
confidence: 99%
“…As mentioned earlier, the combination of the NIR laser lights near 850 nm and the InGaAs detector-based spectrometer allowed the observation of water contents in mineral tissues, including dental hard tissues and bones [22,23]. Mineral tissues appeared more fluorescent than stratum corneum, and were challenging for Raman measurement using visible lights.…”
Section: Water Contents In Mineral Tissuesmentioning
confidence: 99%
“…Unal et al demonstrated that the InGaAs spectrometer designated for 1064 nm Raman spectroscopy can be combined with 852 nm laser to probe hydrations in bone tissues [22]. Yang and He et al modified the system with a 866 nm laser and demonstrated water detection in other biological tissues, including animal skin, human teeth, and fruits [23][24][25]. For example, the Raman spectrum acquired with an InGaAs Raman spectrometer under 866/1064 nm dual excitation (red curve) shows strong signals from CH and OH bonds.…”
Section: Introductionmentioning
confidence: 99%
“…The micromorphologies of the mineralized tissues in enamel are frequently measured by electron microscopy or computed tomography-based technologies which, however, suffer from ionizing radiation hazards, expensive devices as well as sophisticated sample preparation [9]. Noninvasive spectroscopic techniques such as optical coherence tomography (OCT) and Raman spectroscopy have recently been developed as powerful analytical tools for the mineralized microstructures of tooth organs [10][11][12][13][14][15][16]. OCT is a nondestructive, cross-sectional imaging tool that is capable of supplying depth-resolved structural information of dental enamel with micrometer resolution [10].…”
Section: Introductionmentioning
confidence: 99%